LEGO Jurassic World collection [videorecording (DVD)] (Universal, 2025)
The Indominus Escape: When Simon Masrani accidentally destroys one of the park's main attractions, he calls upon his trusted employee Claire Dearing and the rugged dinosaur trainer Owen Grady to save the day.